Evaluating the Revised American Society for Gastrointestinal Endoscopy Guidelines for Common Bile Duct Stone Diagnosis - Jake S. Jacob; Michelle E. Lee; Erin Y. Chew; Aaron P. Thrift; Robert J. Sealock (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims The American Society for Gastrointestinal Endoscopy (ASGE) revised its guidelines for risk stratification of patients with suspected choledocholithiasis. This study aimed to assess the diagnostic performance of the revision and to compare it to the previous guidelines. Methods We conducted a retrospective cohort study of 267 patients with suspected choledocholithiasis. We identified high-risk patients according to the original and revised guidelines and examined the diagnostic accuracy of both guidelines. We measured the association between individual criteria and choledocholithiasis. Results Under the original guidelines, 165 (62%) patients met the criteria for high risk, of whom 79% had confirmed choledocholithiasis. The categorization had a sensitivity and specificity of 68% and 55%, respectively, for the detection of choledocholithiasis. Under the revised guidelines, 86 (32%) patients met the criteria for high risk, of whom 83% had choledocholithiasis. The revised categorization had a lower sensitivity and higher specificity of 37% and 80%, respectively. The positive predictive value of the high-risk categorization increased with the revision, reflecting a potential decrease in diagnostic endoscopic retrograde cholangiopancreatograpies (ERCPs). Stone visualized on imaging had the greatest specificity for choledocholithiasis. Gallstone pancreatitis was not associated with the risk for choledocholithiasis. Conclusions The 2019 revision of the ASGE guidelines decreases the utilization of ERCP as a diagnostic modality and offers an improved risk stratification tool.